2020
DOI: 10.1007/s00330-020-07223-8
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic accuracy of spleen stiffness to evaluate portal hypertension and esophageal varices in chronic liver disease: a systematic review and meta-analysis

Abstract: Objectives To systematically review studies on the diagnostic accuracy of spleen stiffness measurement (SSM) for the detection of clinical significant portal hypertension (CSPH), severe portal hypertension (SPH), esophageal varices (EV), and high-risk esophageal varices (HREV) in patients with chronic liver diseases (CLD). Methods Through a systematic search, we identified 32 studies reporting the accuracy of SSM for the diagnosis of portal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 62 publications
2
40
0
1
Order By: Relevance
“…Hepatosplenomegaly is manifested by an increase in the liver and spleen size, occurs often in viral hepatitis, cholestasis, biliary cirrhosis and hereditarily determined storage diseases. Structural and functional disorders of the spleen are caused by pathological changes in the mechanisms of cellular filtration of blood, antigen elimination, hematopoiesis and deposition of blood cells [1,2]. The entry of infectious antigens and cellular debris through the portal vein into the liver from the digestive tract leads to an immediate response of the liver immune cellsmacrophages of the reticuloendothelial system, which are the first line of defense against foreign antigens [3].…”
Section: Methodsmentioning
confidence: 99%
“…Hepatosplenomegaly is manifested by an increase in the liver and spleen size, occurs often in viral hepatitis, cholestasis, biliary cirrhosis and hereditarily determined storage diseases. Structural and functional disorders of the spleen are caused by pathological changes in the mechanisms of cellular filtration of blood, antigen elimination, hematopoiesis and deposition of blood cells [1,2]. The entry of infectious antigens and cellular debris through the portal vein into the liver from the digestive tract leads to an immediate response of the liver immune cellsmacrophages of the reticuloendothelial system, which are the first line of defense against foreign antigens [3].…”
Section: Methodsmentioning
confidence: 99%
“…14 Spleen stiffness measurement (SSM) correlates well with the presence of esophageal varices and CSPH, as demonstrated recently in a meta-analysis of 32 studies. 15 This is particularly helpful when liver stiffness is between 15 and 20 kPa. 14 A spleen stiffness <21 kPa rules out CSPH while a value $ 50 kPa rules in CSPH.…”
Section: Elastographymentioning
confidence: 99%
“…Currently, the gold standard for defining CSPH is hepatic venous pressure gradient (HVPG) measurement or esophagogastroduodenoscopy (EGD) to detect the presence of varices. Measurement of the HVPG is invasive and costly 19 . Furthermore, although LSM and platelet count serve as good noninvasive predictors of CSPH, correlation with severity is lost when HVPG is >10 mm Hg, leading to underestimating CSPH and decompensation 17 .…”
Section: Clinical Use Of Ssmmentioning
confidence: 99%
“…Measurement of the HVPG is invasive and costly. 19 Furthermore, although LSM and platelet count serve as good noninvasive predictors of CSPH, correlation with severity is lost when HVPG is >10 mm Hg, leading to underestimating CSPH and decompensation. 17 For example, Vermehren et al 7 showed that using ARFI, SSM is more accurate than LSM in predicting large EVs.…”
Section: Determining the Presence Of Csph And Evsmentioning
confidence: 99%